The Role of Educational Counselors in Reducing School Bullying from Their Perspective - علي سهام سعد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The goal of the current research is to identify the role of educational counselors in reducing school bullying from their point of view. The research sample consisted of (150) male and female counselors. The results of the research showed that there is a statistical significance in the role of educational counselors in reducing school bullying from their point of view, and there are no significant differences. Statistical significance at the level of (0.5) in the role of educational counselors in reducing school bullying from their point of view is due to the gender variable.